1993
DOI: 10.1128/iai.61.1.332-334.1993
|View full text |Cite
|
Sign up to set email alerts
|

Relative avidity of serum immunoglobulin G antibody for the fimbria antigen of Actinobacillus actinomycetemcomitans in patients with adult periodontitis

Abstract: The relative avidity of serum immunoglobulin G antibody for the fimbria antigen of Actinobacillus actinomycetemcomitans was assessed by diethylamine dissociation enzyme-linked immunosorbent assay in patients with adult periodontitis. High-titer sera from patients not harboring A. actinomycetemcomitans had significantly higher avidities for the fimbria antigen than did high-titer sera from patients with A. actinomycetemcomitans in their periodontal pockets. The elicited antibodies against the fimbria antigen ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Additionally, Bolstad et al (1990) demonstrated an elevated frequency of responses to selected protein antigens in disease patients when compared to normal subjects. More specific investigations have shown elevations in serum antibody to 29 kDa , 64 kDa (Nakano et al 1995), and 75 kDa (Saito et al 1993) antigens in various diseased patients. Therefore, irrespective of the patient population investigated, or the antigen preparation examined, there appear distinct similarities in the characteristics of the human serum antibody to protein antigens of A. actinomycetemcomitans.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Bolstad et al (1990) demonstrated an elevated frequency of responses to selected protein antigens in disease patients when compared to normal subjects. More specific investigations have shown elevations in serum antibody to 29 kDa , 64 kDa (Nakano et al 1995), and 75 kDa (Saito et al 1993) antigens in various diseased patients. Therefore, irrespective of the patient population investigated, or the antigen preparation examined, there appear distinct similarities in the characteristics of the human serum antibody to protein antigens of A. actinomycetemcomitans.…”
Section: Discussionmentioning
confidence: 99%
“…However, an analysis of the frequency of patient sera that bound to antigenic outer membrane proteins showed that the IgG subclass distribution was IgG2 > IgG3 > IgG1 >> IgG4. Serum IgG antibody binding to 29 (383), 64 (238), 75 (296) and to 28, 38, 54, 58, 75, and 90 kDa (60) outer membrane proteins from periodontitis patients has been shown to be signi®cantly higher than for sera from healthy subjects. Beikler et al (15) monitored the antibody subclass responses to a 110 kDa A. actinomycetemcomitans outer membrane protein in periodontitis patients 24 months after receiving full mouth scaling and/or antimicrobial therapy followed by supportive periodontal therapy.…”
Section: Other Antigenic Outer Membrane Proteinsmentioning
confidence: 99%
“…The sera from patients with adult periodontitis had statistically significantly higher IgG titers against A. actinomycetemcomitans 310-a fimbriae than did sera from periodontally healthy individuals, regardless of infection by the microorganisms in periodontal pockets. Saito et al [4] also found that sera from A. actinomycetemcomitans culture-negative patients with elevated titers of IgG against fimbriae had significantly higher avidity for the fimbriae antigen than did sera from A. actinomycetemcomitans culture-positive patients with elevated titers. These results led us to the hypothesis that the IgG with high avidity to fimbriae antigen elicited by the initial contact with A. actinomycetemcomitans played a role in clearing the organism from the periodontal pockets of these patients.…”
Section: Discussionmentioning
confidence: 96%
“…Al-though the cells of freshly isolated A. actinomycetemcomitans strains have been shown to possess fimbriae [9-111, the roles of these fimbriae and antibodies to the antigen in colonization have not been clearly established. To examine the role of IgG antibody to A. actinomycetemcomitans fimbriae, Saito et al [4] in our laboratory examined the relative avidity of serum IgG antibody in patients for the fimbrial antigens. The sera from patients with adult periodontitis had statistically significantly higher IgG titers against A. actinomycetemcomitans 310-a fimbriae than did sera from periodontally healthy individuals, regardless of infection by the microorganisms in periodontal pockets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation